Financial Capital and the Fantastic - Grgas-Mufa, Stipe (2012)
The presentation designated the present moment as one marked by the dominance of finance capital Furthermore it was argued that the complexity of finance gesture to the fantastic. A number of literary works were referenced to corroborate this claim.
Projekt MZOS
ENG